Alcohol use in adolescence as a risk factor for overdose in the 1986 Northern Finland Birth Cohort Study - Koivisto Maarit K.; Miettunen Jouko; Levola Jonna; Mustonen Antti; Alakokkare Anni-Emilia; Salom Caroline L.; Niemelä Solja (OXFORD UNIV PRESS, 2022)
Background Overdoses and poisonings are among the most common causes of death in young adults. Adolescent problem drinking has been associated with psychiatric morbidity in young adulthood as well as with elevated risk for suicide attempts. There is limited knowledge on adolescent alcohol use as a risk factor for alcohol and/or drug overdoses in later life.
Methods Here, data from The Northern Finland Birth Cohort 1986 study with a follow-up from adolescence to early adulthood were used to assess the associations between adolescent alcohol use and subsequent alcohol or drug overdose. Three predictors were used: age of first intoxication, self-reported alcohol tolerance and frequency of alcohol intoxication in adolescence. ICD-10-coded overdose diagnoses were obtained from nationwide registers. Use of illicit drugs or misuse of medication, Youth Self Report total score, family structure and mother's education in adolescence were used as covariates.
Results In multivariate analyses, early age of first alcohol intoxication [hazard ratios (HR) 4.5, 95% confidence intervals (CI) 2.2-9.2, P < 0.001], high alcohol tolerance (HR 3.1, 95% CI 1.6-6.0, P = 0.001) and frequent alcohol intoxication (HR 1.9, 95% CI 1.0-3.4, P = 0.035) all associated with the risk of overdoses. Early age of first intoxication (HR 5.2, 95% CI 1.9-14.7, P = 0.002) and high alcohol tolerance (HR 4.4, 95% CI 1.7-11.5, P = 0.002) also associated with intentional overdoses.
Conclusions Alcohol use in adolescence associated prospectively with increased risk of overdose in later life. Early age of first intoxication, high alcohol tolerance and frequent alcohol intoxication are all predictors of overdoses.